Design, Analysis, Optimization, Manufacturing, and Testing of a 2U Cubesat - Andreas Ampatzoglou; Vassilis Kostopoulos (International Journal of Aerospace Engineering)
The design optimization, development, and verification by analysis and testing of the 1st Greek cubesat, developed by the University of Patras and Libre Space Foundation (UPSat (University of Patras Satellite)), is presented. The key innovative approach includes the replacement of the aluminum side faces with structural composite components, keeping the commonly used aluminum frame. A “hybrid” double-unit (2U) cubesat structure was optimized, built, and tested for all launch and thermal loads/specifications required for launch and mission operations as imposed from the EU-funded FP7-QB50 project. Results show that the new design of the structure using CFRP can offer similar levels of performance in terms of stiffness, while saving 30% of the mass, for the entire cubesat platform.